Pastoralia of the Church: The Call of Duty for Pastoral Counseling for Congregations experiencing Economic Problems - Apin Militia Christi (Bisma The Journal of Counseling, 2022)
The financial crisis is a problem faced by all human beings, including Christian children. As a result of Covid-19, the economic recession and the decline in the selling value of goods have caused financial problems to get worse. In responding to this problem, a church strategy is needed in the religious sphere to overcome the psychological impact on the congregation. This research aims to determine the service strategy for the Bethel Indonesia Kasih Church congregation to the congregation experiencing the financial crisis. The research method used is phenomenological qualitative with data collection techniques through interviews and observations. The results of the study indicate that the forms of pastoral vocation that can do by church counselors to overcome the congregation's financial crisis are (i) strengthening the congregation's faith in God's providence; (ii) teaching a positive attitude in viewing the financial crisis; (iii) preparing a forum for entrepreneurship; (iv) provide job opportunities for counselees; (v) teach about being a good producer.